2016
DOI: 10.1051/matecconf/20178703008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activated carbon in PSF-PEI-Ag symmetric membrane

Abstract: Abstract. Polysulfone (Psf) composite membrane consist of activated carbon, polyethyleneimine and silver nitrate was prepared by phase inversion. The activated carbon (AC) act as adsorbent to adsorb heavy metal present in synthetic waste water while polysulfone membrane act as support. Phase inversion was carried out on different composition of activated carbon from 0 to 0.9% while other component are remain constant. The surface morphology of composite membrane was characterized by scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Zheng et al (2014) the Langmuir model with a maximum adsorption capacity of 161.29 mg Cu 2+ /g of the membrane. Said et al (2015) fabricated active carbon (AC) membrane supported on polysulfone (PSF) composite membrane that consisted of polyethyleneimine and silver nitrate via phase inversion. The activated carbon (AC) acted as adsorbent to adsorb heavy metal present in synthetic waste water.…”
Section: Polymeric Membranes For Membrane Adsorptionmentioning
confidence: 99%
“…Zheng et al (2014) the Langmuir model with a maximum adsorption capacity of 161.29 mg Cu 2+ /g of the membrane. Said et al (2015) fabricated active carbon (AC) membrane supported on polysulfone (PSF) composite membrane that consisted of polyethyleneimine and silver nitrate via phase inversion. The activated carbon (AC) acted as adsorbent to adsorb heavy metal present in synthetic waste water.…”
Section: Polymeric Membranes For Membrane Adsorptionmentioning
confidence: 99%
“…Carbonaceous materials (carbon nanotubes (CNTs), active carbon (AC), and graphene) are known as potential counterparts in polymer-based composites owing to their high aspect ratio, mechanical strength, compatibility of the carbon matrix with the polymeric structure, and strong interactions and adhesion [113][114][115]. Polysulfone (PSf )/AC composite membrane was fabricated by Said et al [116] and showed that the concentration of AC plays a grave role in support of enhancing heavy metal removal from water. Compared with the above carbonaceous materials, owing to the presence of numerous functional surface groups, graphene oxide (GO) was more widely employed in polymer matrices to enhance heavy metal removal with both high surface area and water solubility [113].…”
Section: Applications Of Nemsmentioning
confidence: 99%
“…A similar structure was observed in an MMM developed by mixing activated carbon (AC), polyethyleneimine, and silver nitrate, which resulted in 35% Cd 2+ adsorption. 165 Further, enhanced elimination of both Cd 2+ and Cu 2+ up to 97% was obtained using polycarbonate (PC) with hydrous manganese oxide (HMO) and alumina nanoparticles in an MMM. The nanoparticles provided higher active adsorption sites and removal for cadmium ions at elevated pH values, whereas they tend to form a positively charged layer at acidic pH, reducing the adsorption efficiency.…”
Section: Uf Membranes For Cadmium Removalmentioning
confidence: 99%
“…164 The mixed matrix approach was also applied by adding activated carbon to the polymer matrix via NIPS. 165 These membranes could target more than 88% pollutant removal. Sam et al demonstrated the green synthesis of CQDs from oats.…”
Section: Smms Synthesis and Fabricationmentioning
confidence: 99%